Interplay of environmental policy and sustainable tourism development in Balkan countries - Banushaj, Aseda; (Dervishi), Doriana Matraku; Jorgji, Etis; Picari, Gentian (Edelweiss Applied Science and Technology, 2025)
Tourism is key to the Balkan economies, yet it is growing rapidly, which raises environmental concerns. This work examines how environmental policy and tourism interact in six Balkan countries: Albania, Bosnia & Herzegovina, Croatia, Montenegro, North Macedonia, and Serbia. By looking at the Environmental Performance Index (EPI), the Travel and Tourism Development Index (TTDI), and the number of tourists, this study shows the tough play between Environmental Policy, sustainability, and green tourism growth. Findings show a strong link between green scores and tourism pull, but gaps are due to roads, ads, and local ways. Croatia shows the good of mixing green care and tourism rules, while Albania’s rise, with okay EPI scores, shows other key parts at play. The study says that green goals need more than green counts; a full plan tying together nature care, road work, and work with local folk is key. The study ends by saying that made-for-green rules, strong rules, and working across borders are a must to align Balkan tourism with big green goals.